Methods of industrial development : with special reference to less developed areas - Winsemius, Albert; Pincus, John A.; European Productivity Agency (Paris : Organisation for Economic Co-operation and Development, 1962)
This is a collection of papers and proceedings of the second study Conference on problems of economic development, organised by the European Productivity Agency of O.E.E.C in Madrid, April 10-15,1961. This was edited by Albert Winsemius and John A. Pincus.
Papers and proceedings of the second study conference on problems of economic development organised by the European Productivity Agency of O E E C, Alcala de Henares, Madrid, April, 1961
lje 24/01/2018
Loans
Keywords: Industrialization; Industrial promotion; Economic development; Industries; Developing countries